Pelatihan Penyusunan Pengabdian Masyarakat pada Sekolah se-Kecamatan Salo - Afriza Rahma Rani; Romi Laspita; Yolanda Pahrul; Nasrul Nasrul; Indriyanto Indriyanto (Universitas Pahlawan Tuanku Tambusai, 2023)
His dedication is motivated by the enactment of the 2013 Curriculum in Indonesia which includes students being required to be able to have critical thinking skills or HOTS. The 2013 curriculum prioritizes learning materials that are given to students up to the metacognitive stage which requires students to be able to predict, design, and predict. This has been explained in the Appendix to Permendikbud Number 21 of 2016, that the dimensions of knowledge based on Bloom's Taxonomy are classified into factual, conceptual, procedural, and metacognitive whose mastery needs to start from the elementary level to the secondary education level. The mechanism of the service method in carrying out activities in general is in the form of planning/preparation, implementation, observation and evaluation, and reflection.